On self-deception: from the perspective of Zhu Xi's moral psychology. - Wang, Kaili (Asian Philosophy, 2021)
In order to construct a satisfactory theory of cheng-yi 誠意 (making thoughts sincere), Zhu Xi 朱熹 develops an account of how self-deception (zi-qi 自欺) is possible—a profound problem that has puzzled many philosophers. In Zhu's opinion, zhi 知 (knowing) can be divided into two categories: a priori knowing and empirical knowing. The further division of empirical knowing defines three sorts of self-deception: (1) the self-deception caused by one's ignorance (wu-zhi 無知), (2) the self-deception caused by one's superficial knowing (qian-zhi 淺知), and (3) the self-deception that may occur when one acquires genuine knowledge (zhen-zhi 真知). In this paper, I will construct a theoretical model of self-deception that follows Zhu's criterial definition of self-deception in Daxue Zhangju 大學章句 (Interpretation of The Great Learning), thereby accounting for the possibility of these three sorts of self-deception. Better understanding of Zhu's conception of self-deception could, moreover, open fruitful avenues for further work on his metaphysics and moral psychology.